Alternative operation models for using a feed‐in terminal as a part of the forest chip supply system for a CHP plant. Issue 11 (28th June 2017) - Väätäinen, Kari; Prinz, Robert; Malinen, Jukka; Laitila, Juha; Sikanen, Lauri
Abstract: The fuel supply of forest chips has to adapt to the annual fluctuations of power and heat generation. This creates inefficiency and unbalances the capacity utilization of the fuel supply fleet in the direct fuel supplies from roadside storages to power and heat generation. Terminals can offer an alternative approach for the fleet management of fuel supplies in terms of smoothing the unbalanced fleet use towards more even year‐round operations. The aim of the study was to compare the supply costs of a conventional direct forest chip supply to an alternative fuel supply with the use of a feed‐in terminal using the discrete‐event simulation method. The influences of the terminal location, terminal investment cost, outbound terminal transport method, terminal truck utilization and quality changes of terminal‐stored forest chips for the fuel supply cost were studied in the case environment. By introducing a feed‐in terminal and a shuttle truck for the transports of terminal‐stored forest chips, the total supply cost was 1.4% higher than the direct fuel supply scenario. In terminal scenarios, the supply costs increased 1–2% if the cost of the terminal investment increased 30%, the distance to the terminal increased from 5 to 30 km or the total annual use of a terminal truck decreased 1500 h. Moreover, a 1 per cent point per month increase in the dry matter loss of terminal‐stored chips increased the total supply cost 1%. The study revealed that with the relatively low additional cost, the feed‐in terminal can be introduced to the conventional forest chip supply. Cost compensation can be gained through the higher annual use of a fuel supply fleet and more secured fuel supply to power plants by decreasing the need for supplement fuel, which can be more expensive at a time of the highest fuel demand. Abstract : Discrete event simulation‐based system analysis model for supply chain logistics of forest chips. Terminal‐based forest chip supply may effectively balance work opportunities and reform the fuel supply towards more stable year‐round activity with relatively low additional costs compared to conventional direct fuel supply. While using terminal supply as a part of forest fuel deliveries, the studied simulation scenarios revealed the impacts of alternative fuel supply setups and quality changes of the fuel on the operation performances and supply costs. It was noted, for example, that a 30% increase in the terminal investment costs or 25 km longer distance to the terminal resulted in 1–2% increase in the supply costs.